Implementasi Jaminan Produk Halal Melalui Sertifikasi Halal Sebagai Service Quality Pada Produk Makanan dan Minuman - Dara Riska Alifia; Aslikha Aslikha; Mohammad Dayat; Sukamto Sukamto (Universitas Islam Raden Rahmat, 2023)
Implementing halal product guarantees through halal certification as service quality is a necessary process that involves the agency administering halal product guarantees. Halal certification as a service quality aims to ensure that the products or services provided by business actors meet the halal standards and requirements stipulated in the Islamic religion. This research examines whether halal certification is used as service quality for food and beverage products for Micro, Small, and Medium Enterprises in the Sekar Association, Purwosari District, Pasuruan Regency. The type of research used by researchers is qualitative research using a descriptive approach. At the same time, the research instruments used in this study were observation, interviews, and documentation. From the study results, it was found that business actors have fulfilled the requirements set out in Islam, which in turn can increase consumer confidence and business reputation. Halal certification as a service quality can be necessary in building good business relationships with consumers who want products or services that comply with halal principles.